The influence of artificial intelligence on the AISs efficiency: Moderating effect of the cyber security - Alrfai, Mohammad Motasem; Alqudah, Hamza; Lutfi, Abdalwali; Al-Kofahi, Mahmoud; Alrawad, Mahmaod; Almaiah, Mohammed Amin (Cogent social sciences, 2023)
The study designed to identify the influence of artificial intelligence on the efficiency of Accounting Information Systems (AIS) in the Jordanian industial companies, where the descriptive analytical approach was used. The study population included all Jordanian industrial companies listed in Amman Stock Exchange, includes (55) industrial companies. The respondents includes the managers, where (275) questionnaires were distributed to the study respondents electronically, with an average of (5) questionnaires for each company, and retrieved 142 valid questionnaires for statistical analysis. The results presented that there is a significant and positive effect of artificial intelligence's dimensions (i.e. expert systems, genetic algorithms, intelligent agents) on the efficiency of AIS in Jordanian industrial companies. But the resule revealed that neural network as an artificial intelligence's dimensions have non-significant effect on the efficiency of AISs. The result also found that the effective application of cyber security moderates the relationship between artificial intelligence and the the efficiency of AIS positively. Given the importance of the industrial companies' sector in the context of Jordan, the results are useful for these companies with regard to the issue of AIS efficiency and the role of artificial intelligence applications in this efficiency. The results also highlighted the importance of the effective application of cyber security in such a technological era. To the knowledge of the authors, this study is one of the first to address cybersecurity as a moderating variable on the relationship between artificial intelligence applications and AIS efficiency in industrial companies in Jordan, a developing country.